Application of the Ar Rasyid Method to Improve Al-Qur'an Memorization at Madrasah Ibtidaiyah - Endah Puji Hastuti; Siti Rohimah (South Sulawesi Education Development (SSED), 2024)
This research aims to find out how to apply the Ar Rasyid method to improve memorization of the Al-Qur'an at MI Muhammadiyah Miri, Nogosari. This research is a qualitativ research. The research subjects involved madrasa heads, tahfidz teachers, and students. The data collection techniques used in this research used observation, interviews and documentation. Data analysis uses the Miles and Huberman analysis model called interactive analysis. This analysis is divided into several stages: data collection, data reduction, data presentation, and drawing conclusions. The results show that the application of the air rasyid method involves several stages: Determining memorization targets, conveying motivation, about the virtues of living close to the Al-Qur'an, conveying memorization material and practicing memorizing the Al-Qur'an. By implementing the Ar Rasyid method, students are able to improve their memorization. Every year, this madrasah can graduate its students from each juz they have completed. One of the advantages of applying the Ar rasyid method is that students are more motivated and develop a strong intention to read the Koran because of the provision of ice breaking. However, the application of this method still has many shortcomings, including the lack of books that discuss the Ar Rasyid method. The existing books are still in the original Arabic form, so there are still many Ustadz who don't understand the Ar rasyid method.